Antiplatelet agents in stroke prevention - Weber, R.; Weimar, C.; Diener, H.-C. (Hämostaseologie, 2009)
In primary prevention, aspirin reduces the risk of stroke but not of myocardial infarction in women while in men only the risk of myocardial infarction but not stroke could be significantly reduced. Only aspirin has been shown to be safe and effective in large randomized trials in the first 48 hours after ischemic stroke. Aspirin/dipyridamole and clopidogrel both reduce the risk of a combined cardiovascular outcome in long-term secondary prevention compared to aspirin alone. More potent antiplatelet drugs or combination of aspirin and clopidogrel prevent more ischemic events, but also lead to more bleeding complications. No benefit of oral anticoagulants could be shown in patients with non-cardioembolic stroke. In patients with atrial fibrillation oral anticoagulation is more effective than aspirin in stroke prevention. The choice between oral anticoagulants and aspirin in these patients depends on age and the individual risk factor profile. Patients with symptomatic intracranial stenosis have a higher risk of intracerebral bleeding with oral anticoagulation compared to high dose aspirin. Aspirin is the recommended treatment in stroke patients with a patent foramen ovale.
Keywords: Ischaemic stroke; transient ischaemic attack; antiplatelet; primary prevention; secondary prevention; anticoagulation